Types and Functions of Code Mixing in Fanfare Song Lyrics by TWICE - Kadek Danu Bimantara; Putu Dewi Merlyna Yuda Pramesti; Yeni Yeni (Global Education Journal, 2026)
Code-mixing is a common linguistic phenomenon in popular music, particularly in Japanese-language songs performed by Korean pop (K-Pop) artists, whose blending of Japanese and English lyrics reflects globalized and multicultural communication strategies. This study aims to identify and describe the types and functions of code-mixing found in the lyrics of TWICE's Japanese song Fanfare, focusing on the linguistic form as well as the pragmatic function of the code-mixed elements within the lyrics. This research employed a descriptive qualitative approach using Muysken's (2000) theory of code-mixing types and Appel & Muysken's (2005) theory of code-mixing functions; the data, obtained from the song's official lyrics published on Spotify and Genius, were collected through a note-taking observation method and analyzed through identification, classification, and functional analysis, with Japanese established as the matrix language. The findings revealed 17 instances of code-mixing, consisting of seven insertion-type and ten alternation-type occurrences, while no instances of congruent lexicalization were identified due to the structural differences between Japanese and English. Furthermore, 27 occurrences of code-mixing functions were found, comprising expressive (11), directive (7), phatic (4), poetic (4), and referential (1) functions. The expressive function was the most dominant, indicating that code-mixing in Fanfare primarily serves to express feelings and emotions in conveying the song's motivational message. These findings confirm that code-mixing in song lyrics is not a coincidental form of language variation but a deliberate, functional linguistic strategy that strengthens meaning and communicative appeal.